The coastal protection and blue carbon benefits of hybrid mangrove living shorelines. (1st April 2023) - Morris, Rebecca L.; Fest, Benedikt; Stokes, Debra; Jenkins, Charlotte; Swearer, Stephen E.
Abstract: Hybrid living shorelines use a combination of engineered structures with natural ecosystems to achieve coastal protection and habitat restoration outcomes, with added co-benefits such as carbon sequestration. Rock fillets constructed along eroding estuarine banks are designed to accumulate sediment, establish mangroves, and stabilise the shoreline. There is, however, a lack of data to support whether rock fillets are achieving these goals. We used a chronosequence of rock fillets to determine their effect on mangrove development, bank stabilisation and carbon sequestration in four estuaries in New South Wales, Australia. Aboveground biomass and adult density increased with age of rock fillets, and mangrove structure was similar to a natural fringing mangrove after 15 years. The rock fillets accumulated sediment, which reduced the eroded estuary bank height, however, little effect of the fillets on bank slope was observed. Sediment carbon stocks were not different between rock fillets, eroding estuary banks and natural fringing mangroves. Rock fillet design had a significant effect on mangrove structure and coastal protection function, with greater wave transmission through lower rock fillets, suggesting design optimisation is needed. As the construction cost of the rock fillets was equal or less than traditional rock revetments, where suitable they present a more economic and environmentally sustainable solution to estuarine erosion management. Highlights: Hybrid living shorelines can provide coastal protection and habitat restoration outcomes. Rock fillets were successful at accumulating sediment and establishing mangroves. Mangrove structure within rock fillets was similar to natural mangroves after 15 years. There was no effect of the rock fillets on blue carbon accumulation. Technical guidance can inform large-scale application of rock fillets for nature-based coastal defence.